Understanding the role of oxylipins in Cannabis to enhance cannabinoid production - Gayathree I. Senevirathne; Gayathree I. Senevirathne; Anthony R. Gendall; Anthony R. Gendall; Anthony R. Gendall; Anthony R. Gendall; Kim L. Johnson; Kim L. Johnson; Kim L. Johnson; Matthew T. Welling; Matthew T. Welling; Matthew T. Welling (Frontiers in Plant Science)
Phytocannabinoids are medically important specialized defense compounds that are sparsely distributed among plants, yet Cannabis sativa can synthesize unprecedented amounts of these compounds within highly specialized surface cell factories known as glandular trichomes. The control mechanisms that allow for this high level of productivity are poorly understood at the molecular level, although increasing evidence supports the role of oxylipin metabolism in phytocannabinoid production. Oxylipins are a large class of lipid-based oxygenated biological signaling molecules. Although some oxylipins are known to participate in plant defense, roles for the majority of the ca. 600 plant oxylipins are largely unknown. In this review, we examine oxylipin gene expression within glandular trichomes and identify key oxylipin genes that determine the fate of common lipid precursors. Mechanisms by which oxylipins may be interacting with phytocannabinoid metabolism, as well as specialized plant metabolism more broadly, are discussed and a model summarizing these contributions proposed.